eLearning: Exploring Digital Futures in the 21st Century - Glenn Finger (MDPI AG, 2014)
In a globalised knowledge economy, enabled by an increasingly pervasive digital, networked world, eLearning possibilities are being explored by educational institutions. Learning and teaching is now able to be designed to enable learning anywhere and at anytime. This opens up exciting possibilities as well as challenges. Consequently, this special issue aimed to provide evidence-based guidance through conceptual and research papers on eLearning and digital futures in the 21st century. [...]